Combining Intraoral and Face Scans for the Design and Fabrication of Computer-Assisted Design/Computer-Assisted Manufacturing (CAD/CAM) Polyether-Ether-Ketone (PEEK) Implant-Supported Bars for Maxillary Overdentures. (22nd August 2019) - Mangano, Francesco; Mangano, Carlo; Margiani, Bidzina; Admakin, Oleg
Abstract : Purpose . To present a digital method that combines intraoral and face scanning for the computer-assisted design/computer-assisted manufacturing (CAD/CAM) fabrication of implant-supported bars for maxillary overdentures. Methods . Over a 2-year period, all patients presenting to a private dental clinic with a removable complete denture in the maxilla, seeking rehabilitation with implants, were considered for inclusion in this study. Inclusion criteria were fully edentulous maxilla, functional problems with the preexisting denture, opposing dentition, and sufficient bone volume to insert four implants. Exclusion criteria wereage < 55 years, need for bone augmentation, uncompensated diabetes mellitus, immunocompromised status, radio- and/or chemotherapy, and previous treatment with oral and/or intravenous aminobisphosphonates. All patients were rehabilitated with a maxillary overdenture supported by a CAD/CAM polyether-ether-ketone (PEEK) implant-supported bar. The outcomes of the study were the passive fit/adaptation of the bar, the 1-year implant survival, and the success rates of the implant-supported overdentures. Results . 15 patients (6 males, 9 females; mean age68.8 ± 4.7   years ) received 60 implants and were rehabilitated with a maxillary overdenture supported by a PEEK bar, designed and milled from an intraoral digital impression. The intraoral scans were integrated with face scans, in order to design each bar with all available patient data (soft tissues, prosthesis, implants, and face) in the correct spatial position. When testing the 3D-printed resin bar, 12 bars out of 15 (80%) had a perfect passive adaptation and fit; in contrast, 3 out of 15 (20%) did not have a sufficient passive fit or adaptation. No implants were lost, for a 1-year survival of 100% (60/60 surviving implants). However, some complications (two fixtures with peri-implantitis in the same patient and two repaired overdentures in two different patients) occurred. This determined a 1-year success rate of 80% for the implant-supported overdenture. Conclusions . In this study, the combination of intraoral and face scans allowed to successfully restore fully edentulous patients with maxillary overdentures supported by 4 implants and a CAD/CAM PEEK bar. Further studies are needed to confirm these outcomes.